Sex and Drugs : Preventing HIV/AIDS among Truckers and Sailors in Georgia - Bakilana, Anne (World Bank, Washington, DC, 2012)
This knowledge brief summarizes the results of a November 2007 study that examined attitudes and approaches toward HIV prevention and care among health and transport sector institutions, non-governmental organizations (NGOs), transport sector workers, and sex workers (SWs) in Georgia. The aim was to identify the unique needs of transport sector workers with respect to HIV so that specific strategies and targeted intervention programs within both the health and transport sectors can be developed. The study was based on two quantitative surveys conducted with truckers, sailors and sex workers in Poti, Batumi and Gori in Georgia, and on qualitative surveys conducted with health and transport sector institutions and NGOs.